Isolation and Characterization of Hydrocarbon Degrading Bacteria from Petrol Contaminated Soil - Talat Yasmeen Mujahid; Abdul Wahab; Safia Hashim Padhiar; Syed Abdus Subhan; Muneera Naz Baloch; Zaid A. Pirzada (Journal of Basic & Applied Sciences, 2015)
Hydrocarbon degrading bacteria were isolated from the petrol contaminated soil of Karachi to determine their biodegradation capabilities of aromatic hydrocarbons such as xylene, phenanthrene, naphthalene, biphenyl and anthracene. Twelve bacterial strains were isolated by culture enrichment technique in Bushnell Hass medium in the presence of petrol. Hydrocarbon degradation capabilities of bacterial strains were assessed by means of enumeration using spread-plate technique. Current study revealed that all of the twelve isolated bacterial strains were able to degrade aromatic hydrocarbons, particularly Pseudomonas sp. SA044, degraded all the tested five aromatic hydrocarbons while Burkholderia sp., Ralstonia sp., Stenotrophomonas sp., Micrococcus sp. and Staphylococcus sp. degraded three or more aromatic hydrocarbons.Naphthalene and phenanthrene were the most degraded aromatic hydrocarbons.